Why boys fail [ saving our sons from an educational system that's leaving them behind - Whitmire, Richard (American Management Association, 2012)
The signs and statistics are undeniable: boys are falling behind in school. Contrary to conventional wisdom, the biggest culprits are not video games, pop culture, or female-dominated schools biased toward girls. The real problem is that boys have been thrust into a bewildering new school environment that demands high-level reading and writing skills long before they are capable of handling them. Lacking the ability to compete, boys fall farther and farther behind. Eventually, the problem gets pushed into college, where close to 60% of the graduates are women. In a time when even cops, constru